Interpersonal Communication Between PUBG Mobile Online Game Players on Team Bee - Gokma Riski Sitorus Pane; Angga Intueri Mahendra (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
The development of technology and information has presented various types of online games, one of which is PUBG Mobile, which is popular among young people and students. In this game, virtual communication plays a crucial role in conveying information, strategy, and emotions when playing together, which has a direct impact on success and victory in the game. In the context of a team game like PUBG Mobile, effective interpersonal communication is a key factor in achieving success. This study aims to investigate the ways of interpersonal communication between players in the PUBG Mobile game. The research method used is descriptive qualitative research, which is systematic and objective. The research sample was selected using a non-probability purposive sampling method. Aspects of communication, such as openness, empathy, support, positive attitude, and equality, will be measured based on the theory proposed by Joseph A. DeVito as research variables. The research results highlight the importance of effective interpersonal communication in achieving success in the game. Key factors such as openness, empathy, support, positive attitude, and equality were identified as elements that shape communication within the team. This research provides insight that effective interpersonal communication directly affects team performance, and players can improve collaboration and coordination in games by paying attention to these factors.